Judicial Resistance: missing part of judicial independence? The case of Poland and beyond - Bojarski, Łukasz (Oñati Socio-Legal Series, 2025)
This article critically examines the concept of "judicial resistance" in Poland between 2015-2023, drawing insights from both Polish and international legal frameworks, jurisprudence, empirical research and literature. The study aims to define and differentiate judicial resistance from other judicial attitudes, interrogate its legal character, and explore whether there exists judges’ right or duty towards such resistance. The article posits a definition for judicial resistance, emphasizing actions—both collective and individual, in-court and out-of-court—taken by judges to counter political endeavors that infringe upon judicial independence and violate the law. A pivotal criterion proposed is that the breach of judicial independence must be illegitimate as per national standards and validated as such. To support this, the article references formal assessments from both national and international bodies. The findings indicate a potential necessity for a broader conceptualization of judicial resistance, suggesting it as a possible safeguard against future erosions of the rule of law.